The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/ene.12950
|View full text |Cite
|
Sign up to set email alerts
|

The impact of non‐motor symptoms on the quality of life of Parkinson's disease patients: a longitudinal study

Abstract: Unlike motor disabilities, NMSs burden, in particular sleep, mood and attention, have a significant impact on the QoL of PD patients over a 2-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
99
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 32 publications
16
99
0
10
Order By: Relevance
“…A study from Singapore [56] reported that sleep, mood, and attention disorders have a significant negative impact on QoL, which is similar to data from Europe [57]. Given that these were the NMS we identified to be most prevalent in Asian patients, it emphasises its importance, the need to address them in clinical practice, and the possible future requirement of ethnicity-based personalised medicine [56]. …”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A study from Singapore [56] reported that sleep, mood, and attention disorders have a significant negative impact on QoL, which is similar to data from Europe [57]. Given that these were the NMS we identified to be most prevalent in Asian patients, it emphasises its importance, the need to address them in clinical practice, and the possible future requirement of ethnicity-based personalised medicine [56]. …”
Section: Discussionsupporting
confidence: 55%
“…Li et al [55] demonstrated, in a cross-sectional study in China, that the domains of sleep/fatigue, mood, gastrointestinal, urinary, and miscellaneous had a particularly meaningful negative impact on the patient's QoL. A study from Singapore [56] reported that sleep, mood, and attention disorders have a significant negative impact on QoL, which is similar to data from Europe [57]. Given that these were the NMS we identified to be most prevalent in Asian patients, it emphasises its importance, the need to address them in clinical practice, and the possible future requirement of ethnicity-based personalised medicine [56].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these NMS are associated with severe disability, shortened life expectancy, reduced quality of life of patients and caregivers, and increased health-care costs [15].…”
Section: Cognitive Impairment In Pdmentioning
confidence: 99%
“…Autonomic dysfunction symptoms significantly impair the quality of life of PD patients, even more than motor symptoms. 6 Autonomic dysfunctions are part of a spectrum of non-motor symptoms in patients with PD. 7 Nonmotor symptoms may precede typical motor features of PD by several years.…”
Section: Introductionmentioning
confidence: 99%